Visualizing Cortical Development and Evolution: A Toolkit Update - Kumamoto, Takuma; Ohtaka-Maruyama, Chiaki (Frontiers in Neuroscience, 2022)
Visualizing the process of neural circuit formation during neurogenesis, using genetically-modified animals or somatic transgenesis of exogenous plasmids, has become a key to decipher cortical development and evolution. In contrast to the establishment of transgenic animals, the designing and preparation of genes of interest into plasmids are simple and easy, dispensing with time-consuming germline modifications. These advantages have led to neuron labeling based on somatic transgenesis. In particular, mammalian expression plasmid, CRISPR-Cas9, and DNA transposon systems, have become widely used for neuronal visualization and functional analysis related to lineage labeling during cortical development. In this review, we discuss the advantages and limitations of these recently developed techniques.